Redefining Refugees in Canada: Comparing Policy Frames for Refugee Health Care Policy in Canada and the United States - Rivera Perez, Vilma Veronica (Université d'Ottawa | University of Ottawa, 2014)
In 2012 the Government of Canada announced a series of changes to the Interim Federal Health Program responsible for health insurance for refugees and asylum seekers in Canada. The reform restricts medical coverage for certain groups, including privately sponsored refuges and asylum seekers with pending or denied decisions. Despite strong opposition from medical professionals, refugee advocates and provincial governments, the Government defended its decision on the grounds that the previous system was “too generous” and it would be unfair to grant medical insurance coverage beyond that offered to Canadians. Similarly, in the United States the Refugee Medical Assistance Program also distinguishes health coverage eligibility between refugees and asylum seekers, offering comprehensive medical coverage for refugees for an eight month period upon arrival. In this paper I conduct a comparative analysis between Canada and the United States in the area of refugee health care policies. The analysis concludes Canada is moving closer to emulating the existing refugee health policy in the United States. In addition, in this paper I argue that the ways legitimate refugees have been framed in the United States have also influenced recent shifts in the way Canada has narrowed the scope of who qualifies as a legitimate refugee and what state services these persons are eligible to receive.